CSCW: designing abstract scripting language for role transition management / Zainura Idrus ... [et al.] - Idrus, Zainura; Idrus, Zanariah; Ismail, Siti Nurbaya; Z. Abidin, Siti Zaleha; Omar, Nasiroh (2018)
The nature of tasks and users in computer support collaborative work (CSCW) are dynamic. They usually last for a short period of time and their existence is unpredictable partly due to dynamic data. The uncertainty is suitable to be managed via role-based management where a virtual entity called role is used as a medium between users and tasks. Tasks are assigned directly to roles and not users. Any changes of user will have a minimum impact to role structure. Therefore, users are independent from tasks. The changes of role between users are called role transition and such transition must be flexible to cater for dynamic environment. Thus, the system must support fast development and maintenance. Even though flexibility can be in various forms, this paper supports flexibility through scripting language where the focus is on language abstraction. To achieve the objective, flexibility is explored and viewed from two perspectives which are system and programming language to identify their behaviours via content analysis methods. Since domain specific language is uniquely identified by its abstraction, it is explored in detail. However, most abstraction languages are not abstract enough. Thus, this research has introduced a new model of abstraction. The model introduces a new concept of plug-in and multiple instructions per-statement to increase language abstraction. The knowledge gained is used to design a new set of language constructs through language abstraction which is flexible via plug-in and multiple instructions per-statement mechanisms. Indeed, the mechanisms are very much needed in supporting role transition management in rapid prototyping of CSCW systems.